The Application of Dragon Fruit Peels as a Dye in Red Velvet Cake - Dianka Wahyuningtias (Bina Nusantara University, 2015)
Red Dragon fruit peel that has a high antioxidant content is very useful and suitable processed into natural coloring in household industry are easily processed. One product to apply it is the Red Velvet Cake. Red Velvet Cake is basically uses natural coloring from the bits fruit and instant food coloring. This discussion will create a research that is attempting to replace the instant food coloring and natural food coloring from the bit that is commonly used in Red Velvet Cake by making use of the Dragon fruit that is considered to be food wastes. This research aims to provide a new alternative natural food coloring in the Red Velvet Cake. Experimental research is used by doing experiments and planned and systematic testing to Red Velvet Cake, and by collecting primary data and secondary data as well. All data is presented in a descriptive with SPSS. From the results of mean average can be inferred that the Red Velvet Cake using natural food coloring from Red Dragon fruit is acceptable to the community.